CEACAM3—A Prim(at)e Invention for Opsonin-Independent Phagocytosis of Bacteria - Bonsignore, Patrizia; Kuiper, Johannes W. P.; Adrian, Jonas; Goob, Griseldis; Hauck, Christof R. (Frontiers in Immunology, 2020)
Phagocytosis is one of the key innate defense mechanisms executed by specialized cells in multicellular animals. Recent evidence suggests that a particular phagocytic receptor expressed by human polymorphonuclear granulocytes, the Carcinoembryonic Antigen-related Cell Adhesion Molecule 3 (CEACAM3), is one of the fastest evolving human proteins. In this focused review we will try to resolve the conundrum, why a conserved process such as phagocytosis is conducted by a rapidly changing receptor. Therefore, we will first summarize the biochemical and structural details of this immunoglobulin-related glycoprotein in the context of the human CEACAM family. The function of CEACAM3 for the efficient, opsonin-independent detection and phagocytosis of highly specialized, host-restricted bacteria will be further elaborated. Taking into account the decisive role of CEACAM3 in the interaction with pathogenic bacteria, we will discuss the evolutionary trajectory of the CEACAM3 gene within the primate lineage and highlight the consequences of CEACAM3 polymorphisms in human populations. From a synopsis of these studies CEACAM3 emerges as an important component of human innate immunity and a prominent example of a dedicated receptor for professional phagocytosis.